'Providence' or 'religious fatalism'? A distinction without a difference in disasters research?. Issue 3 (3rd May 2020) - Abbott, Roger P.
ABSTRACT: One of the principle theological themes that emerged from my narrative data, gathered from interviewing survivors of the 2010 Haiti earthquake, was that of divine providence. Although the terms 'fatalism' and 'providence' were never explicitly used by the researchers or the participants, the language interviewees used and the meaning they expressed would be categorised in traditional theological terms under divine providence. Yet, when social scientists commentate upon the same beliefs, they tend to use the term 'religious fatalism'. What could appear to be a distinction without a difference, however, can actually represent a misunderstanding with possible egregious consequences. With reference to a discussion between a social geographer colleague and myself as a practical theologian, I seek to explore the dilemma that can arise over use of different terms when referring to the same incident by social scientists and theologians.